A boundary-only integral equation method for parabolic problems of another class of anisotropic functionally graded materials. (March 2021) - Azis, Moh. Ivan; Abbaszadeh, Mostafa; Dehghan, Mehdi; Solekhudin, Imam
Abstract: In this paper a combined Laplace transform and boundary element method is used to find numerical solutions to problems of another class of anisotropic functionally graded materials which are governed by a variable coefficients parabolic equation. A transformation is used to reduce the variable coefficients equation to a constant coefficients equation, which is then transformed into a boundary-only integral equation. Some examples are considered to show the validity of the analysis, consistency and accuracy of the numerical solutions. A verification for the effect of the anisotropy and inhomogeneity of the material on the solutions is also examined.